Spiro‐OMeTAD‐Based Hole Transport Layer Engineering toward Stable Perovskite Solar Cells. Issue 11 (6th October 2022) - Shen, Ying; Deng, Kaimo; Li, Liang
Abstract: Perovskite solar cells (PSCs) have undergone unprecedented growth in the past decade as an emerging photovoltaic technology. Up till now, the power conversion efficiency of PSCs has exceeded 25% that rivals silicon solar cells and there is still room for further enhancement. However, the development in long‐term stability lags far behind, which remains a great concern for the commercial application in the future. The device instability mainly arises from the functional components, including perovskite film, charge transport layers, and electrodes along with the involved interfaces. As the most widely studied hole transport layer at the current stage, 2, 2′, 7, 7′‐tetrakis(N, N‐di(4‐methoxyphenyl)amino)‐9, 9‐spirobifluorene (Spiro‐OMeTAD) helps contribute to the achievement of record efficiency but it weakens the device stability due to the doping‐induced side effects such as hygroscopicity and ion migration. Great efforts are devoted to boosting the stability of Spiro‐OMeTAD while maintaining excellent photovoltaic performance. In this review, the fundamental properties of Spiro‐OMeTAD have been summarized and the recent advances in engineering Spiro‐OMeTAD‐based hole transport layer for the sake of highly efficient PSCs with enhanced longevity are highlighted. In the end, an outlook for the further optimization of Spiro‐OMeTAD is provided and the issues related to large‐scale production are discussed. Abstract : 2, 2′, 7, 7′‐tetrakis(N, N‐di(4‐methoxyphenyl)amino)‐9, 9‐spirobifluorene (Spiro‐OMeTAD) has been widely applied as an efficient hole transport layer for perovskite solar cells but the issues related to device stability need to be addressed. Here, recent advances in Spiro‐OMeTAD engineering toward improved device stability have been summarized from the perspective of the optimization strategies. Remaining challenges, as well as opportunities for future research are also discussed.